Methods of Synthesis of Regulators for Nonlinear Dynamic Systems (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Methods and algorithms for the synthesis of regulators for nonlinear dynamic systems are given, based on various approaches to the formation of a control device. We considered synthesis methods based on phase space, Lyapunov function method, vibration control, feedback linearization method, velocity gradient method, lag feedback method, adaptive, robust, intelligent approaches, fuzzy logic, systems with a variable structure, etc. All the methods of synthesis of nonlinear regulators discussed above give a solution to the problem only for rather narrow classes of objects. Therefore, the problem of building regulators for nonlinear systems in many cases has not yet been solved.